FEATURES OF INTEGRATION AND SOCIAL ADAPTATION OF UKRAINIAN REFUGEE CHILDREN IN THE GERMAN EDUCATION SYSTEM - Sitkar , Victor; Sitkar , Stepan (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article examines the modern experience and features of the educational system in Germany regarding the specifics of integration and social adaptation of Ukrainian children of forced refugees due to the war carried out by the Rashists in Ukraine. A description of various approaches to the organization of education of forced migrants and refugees in German schools has been made.